An Integrated Model for Online-Offline Classroom for Optimizing Academic Management and Enhancing Student Learning Outcomes - Lin Mei (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This study aims to develop an integrated online-offline classroom model based on academic management to enhance student learning outcomes at NanHang JinCheng College, Nanjing, China. Data were collected through a qualitative methodology from 392 students and 220 teachers using structured questionnaires. Descriptive statistical analysis focused on key dimensions such as student engagement, pedagogical flexibility, and academic management’s role in optimizing learning performance. The findings indicate high student satisfaction in collaborative learning, knowledge application, and group discussions. However, moderate satisfaction was observed regarding diverse learning resources and proactive feedback-seeking behaviors. Teachers exhibited strong confidence in integrating hybrid learning models yet showed limited adaptation of lessons based on real-time student feedback. Academic management emerged as a crucial factor in shaping learning outcomes, highlighting the need for enhanced assessment tools and adaptive learning strategies. The study concludes that while the proposed hybrid model significantly improves student achievement, its long-term effectiveness depends on continuous professional development, optimized resource utilization, and dynamic adjustments through decision-making approaches. Integrating uncertainty modeling and intelligent learning analytics can refine hybrid learning frameworks for sustainable educational innovation.